The shape of fringing tidal flats in engineered estuaries - Hanssen, Jill L. J.; van Prooijen, Bram C.; van Maren, Dirk S. (Frontiers in Marine Science, 2024)
For the management of estuaries and the preservation of tidal flats it is crucial to understand the tidal flat shape and development. Previous work focused predominantly on the quasi-equilibrium shape of tidal flats along open coasts with a dominant cross-shore flow and wave exposure. This paper evaluates the shape of fringing tidal flats in engineered estuaries, where longshore velocities generally dominate. Using a long-term (20 years) topographic data set of an anthropogenically modified estuary in the Netherlands (the Western Scheldt estuary), we relate key profile shape parameters and changes over time to natural and anthropogenic processes. In an engineered estuary, the tidal flat shape depends on the estuary geometry, hydrodynamic forcings and human interventions. In contrast to open coast tidal flats, the presence of the channel and dominant longshore flow determines the available cross-shore length (accommodation space) of the tidal flat and the shape of the tidal flat. This accommodation space defines the maximum tidal flat height and opportunity for marsh development. We propose the use of the Index of Development, indicating to what extend tidal flats have space to develop. This index is not only influenced by longshore and cross-shore flow, but also (or even more) by hydraulic structures, dike realignments and channel migration. Especially the latter two strongly influence the accommodation space and thereby the maximum tidal flat height and the opportunity for marsh development. For large stretches of the Western Scheldt, the accommodation space is too small, and the majority of the tidal flats do not vertically extent to mean high water. The success of tidal flat and marsh restoration projects depends on the accommodation space.